Knot Architecture for Biocompatible and Semiconducting 2D Electronic Fiber Transistors - Coleman, Jonathan; Carey, Tian (My University, 2024)
Wearable devices have generally been rigid due to their reliance on silicon-based technologies, while future wearables will utilize flexible components for example transistors within microprocessors to manage data. Two-dimensional (2D) semiconducting flakes have yet to be investigated in fiber transistors but can offer a route toward high-mobility, biocompatible, and flexible fiber-based devices. Here, the electrochemical exfoliation of semiconducting 2D flakes of tungsten diselenide (WSe2) and molybdenum disulfide (MoS2) is shown to achieve homogeneous coatings onto the surface of polyester fibers. The high aspect ratio (>100) of the flake yields aligned and conformal flake-to-flake junctions on polyester fibers enabling transistors with mobilities μ ≈1 cm2 V−1 s−1 and a current on/off ratio, Ion/Ioff ≈102–104. Furthermore, the cytotoxic effects of the MoS2 and WSe2 flakes with human keratinocyte cells are investigated and found to be biocompatible. As an additional step, a unique transistor ‘knot’ architecture is created by leveraging the fiber diameter to establish the length of the transistor channel, facilitating a route to scale down transistor channel dimensions (≈100 µm) and utilize it to make a MoS2 fiber transistor with a human hair that achieves mobilities as high as μ ≈15 cm2 V−1 s−1
PUBLISHED
cited By 0
Keywords: Wearable devices; silicon-based technologies; semiconducting flakes